EXCHANGE RATE POLICY: THE EFFECTS OF EXCHANGE RATE VOLATILITY ON THE ECONOMY - Pereira da Silva Leão, Airton; Gustavo Portela dos Santos, Mikael; Melo Costa Simões, Valéria; Borges Alves Pessoa, Solange; Guimarães Bezerra, Thayná (Revista Gênero e Interdisciplinaridade, 2026)
This article addresses initial concepts regarding exchange rates, exchange rate policy, the Brazilian foreign exchange market, and volatility, in order to facilitate and provide the reader with a better understanding of the subject. The Brazilian foreign exchange market is a complex environment; therefore, its stability depends on the good development of the country's economy. Like many countries, the Brazilian foreign exchange market suffers from volatility in exchange rates, which can be detrimental to various sectors of the country. Thus, this work aims to study volatility in order to answer the following question: what are the effects of volatility on the Brazilian economy? Throughout the work, data referring to the second half of 2019 and the first half of 2020 will be presented in order to analyze the volatility of the Brazilian market during this period. The article uses a bibliographic research methodology based on articles related to the topic, of a descriptive nature, given that it offers quantitative data.